Study of fetal doppler velocimetry versus non stress test as predictors of adverse perinatal outcome in high risk pregnancies - K., Hymavathi; P., Prasuna; Rani, Davuluru Sandhya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Pregnancy is a unique, physiologically normal event in a women’s life. Objective of this study was to compare the efficacy of the doppler velocimetry versus non stress test in relation to perinatal outcome in high risk pregnancies. Methods: This is a prospective study conducted in the department of obstetrics and gynaecology, Narayana Medical College and Hospital. 100 women with high risk pregnancy were recruited. All were examined systematically, and Doppler velocimetry and non-stress test were done. Results: All cases were divided into four groups based on NST and doppler velocimetry of umbilical artery and middle cerebral artery. 10% of women had abnormal doppler. Middle cerebral artery doppler abnormality was noted in 3% and CPR abnormality in 3% of women in the study group. 15% had abnormal NST. In Group A, out of 88 patients 9 had fetal compromise. In Group B, out of 5 patients all had fetal compromise. In Group C, out of 4 patients none had fetal compromise. In Group D, all 3 patients had fetal compromise. In Group D, all 3 had neonatal deaths. Average birth weights in Group A was 2.7 kg, in Group B was 2 kg, in Group C was 2.5 kg, in Group D was 1.4 kg. Two (2.2%) newborn in Group A, 4 (80%) newborns in Group B, 3 (100%) in Group had Apgar < 7 at 5 minutes. 4 (4.5%) babies in Group A, 5 (100%) babies in Group B, 3 (100%) babies in Group D were admitted in NICU. Umbilical artery doppler was found to have sensitivity 46.6%, specificity - 94%, PPV - 93%, NPV - 54%. Middle cerebral artery doppler was found to have sensitivity 73.3%, specificity - 90%, PPV - 91.6%, NPV- 69.3%. Conclusions: In present study, highest percentage of perinatal complications and perinatal deaths were seen in groups with abnormal tests of NST and velocimetry. Group D had the worst perinatal outcome.